2020
DOI: 10.1088/1748-0221/15/06/p06001
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence time resolution investigation of BaF2-based H6610 detectors for a digital positron annihilation lifetime spectrometer

Abstract: BaF 2 -based detectors have been used in many fields requiring fast timing, especially in positron annihilation lifetime (PAL) spectroscopy. The performance of a PAL spectrometer is closely correlated with the time response of BaF 2 -based detectors. Therefore, it is important to select scintillation detectors with excellent time resolution. In this work, the coincidence time resolution of BaF 2 -based H6610 detectors was investigated using a digital oscilloscope. The time response of detectors has been optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Through the timing resolution measurements, we confirmed that the timing resolution of the SiPM-based digital PAL spectrometer was different according to the γ-ray energy. The higher the γ-ray energy the better the timing resolution, which well matched the results of previous studies [5,10]. The output pulse of the SiPM is the sum of individual pulses from micro cells so the slope of the pulse is proportional to the number of fired micro cells.…”
Section: Timing Resolution Measurement Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Through the timing resolution measurements, we confirmed that the timing resolution of the SiPM-based digital PAL spectrometer was different according to the γ-ray energy. The higher the γ-ray energy the better the timing resolution, which well matched the results of previous studies [5,10]. The output pulse of the SiPM is the sum of individual pulses from micro cells so the slope of the pulse is proportional to the number of fired micro cells.…”
Section: Timing Resolution Measurement Resultssupporting
confidence: 86%
“…Digital constant fraction discrimination (dCFD) is the most common time pick-off method for measuring the arrival time of the γ-ray in scintillator detectors such as the PAL spectrometer and positron emission tomography (PET) detectors [5,7,14,19]. The principle of dCFD is to determine the arrival time of radiation when the pulse amplitude reaches a specific threshold fraction of the maximum amplitude as shown in figure 2.…”
Section: Digital Fraction Discrimination (Dcfd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Groups in Japan [17,18] and Finland [19,20] recorded the first fully-digital lifetime spectra based on fast digital oscilloscopes. In the following years, many other laboratories [21][22][23][24][25][26] performed a transition from analogue to digital technology. The advantages of digital data acquisition became increasingly visible.…”
Section: General Information On Digitizationmentioning
confidence: 99%